Hybrid Nano-GdF(3) contrast media allows pre-clinical in vivo element-specific K-edge imaging and quantification - Halttunen, Niki (Sci Rep, 2019)
Computed tomography (CT) is a widely used imaging modality. Among the recent technical improvements to increase the range of detection for optimized diagnostic, new devices such as dual energy CT allow elemental discrimination but still remain limited to two energies. Spectral photon-counting CT (SPCCT) is an emerging X-ray imaging technology with a completely new multiple energy detection and high spatial resolution (200 μm). This unique technique allows detection and quantification of a given element thanks to an element-specific increase in X-ray absorption for an energy (K-band) depending on its atomic number. The main contrast media used hitherto are iodine-based compounds but the K-edge of iodine (33.2 keV) is out of the range of detection. Therefore, it is crucial to develop contrast media suitable for this advanced technology. Gadolinium, well known and used element for MRI, possess a K-edge (50.2 keV) well suited for the SPCCT modality. The use of nano-objects instead of molecular entities is pushed by the necessity of high local concentration. In this work, nano-GdF(3) is validated on a clinical based prototype, to be used as efficient in vivo contrast media. Beside an extremely high stability, it presents long lasting time in the blood pool allowing perfusion imaging of small animals, without apparent toxicity.